فن اشتقاق كى لغوى اور معنوى باريكياں : Secrets of Etymology Linguistically and Semantically - Roohi Abbas,; Sumbul Nazir,; Dr. Mussarat Jamal, (Al Manhal Research Journal, 2025)
Etymology is the study of the relationship between two words in their original meaning and structure, identifying how one word relates to the other and is derived from it. Etymology is synonymous with etymology in all other languages. Language: Derivation from the word “shaq” which means to take something from something or to take its half; that is, half of it. The derivation of speech is to take it right and left, and the derivation of a letter from a letter is to take it from it. It is said that someone split speech if he brought it out in the best way. Technically: Its definitions in linguistic terminology are many, including: A branch is taken from a root whose conjugations are based on the letters of that root. Taking one word from another with some change, but with proportion in meaning. Extracting a word from another, if they are suitable in meaning and structure, and different in form. Naming based on derivation: the science of derivation or the standards of language. The first is the well-known one in the books of authors, but the second is closer to the intended meaning. Ibn Faris named his book (Dictionary of Standards of Language) accordingly. The Arabic language is a derivational language of the first degree. Definition and definition of etymology: The science of Arabic semantics, which identifies the origin of words. This definition is closer to orthography. The subject of etymology: knowing the meanings of words and their connection to each other, by referring to the origins of their meanings derived from measuring the meanings of words with similar material. The fruit of the science of etymology: deepening the understanding of the speech of the Arabs, and thus of the speech of the Lawgiver. You will often find commentators making passing references to examples of this science, and many of the authors of the sciences also make passing references to it when explaining some terms and clarifying the derivation therein. The founder and originator of the science of etymology : Ibn Duraid is considered the first to devote a classification to it that includes many of its origins, and Ibn Faris is the one who created its arch with his book, Mu’jam Maqayis al-Lughah, as well as some of the attempts and scattered works before them, especially by Al-Khalil bin Ahmad Al-Farahidi. The ruling on the science of etymology: It is a communal obligation, just as scholars have decided that all instrumental sciences are communal obligations. The merit of the science of derivation: It helps in understanding the religious texts, so there is no doubt that it is a meritorious science, and therefore it is frequently mentioned in books of interpretation and deductions in jurisprudential disputes. Etymology: It is one of the sciences of the Arabic language with rational application. It can be considered a part of the science of (philology), and it shares some topics with (morphology) in one aspect. The difference between them is that the science of morphology studies the apparent weights and the meaning of each weight, while derivation studies the hidden meaning and the connection of meanings in a single material.